2018
DOI: 10.3390/nu10060674
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Healthy Eating Index and Glycemic Index in Multi-Ethnic Colorectal Cancer Families

Abstract: For personalized nutrition in preparation for precision healthcare, we examined the predictors of healthy eating, using the healthy eating index (HEI) and glycemic index (GI), in family-based multi-ethnic colorectal cancer (CRC) families. A total of 106 participants, 53 CRC cases and 53 family members from multi-ethnic families participated in the study. Machine learning validation procedures, including the ensemble method and generalized regression prediction, Elastic Net with Akaike’s Information Criterion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…The study methods were reported before [ 43 , 52 ] and are summarized in the following. We included 30 participants, 15 CRC cases and 15 matched family/friend controls by accessing the California Cancer Registry (CCR) database and other cases through referrals from the community where the study was conducted.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study methods were reported before [ 43 , 52 ] and are summarized in the following. We included 30 participants, 15 CRC cases and 15 matched family/friend controls by accessing the California Cancer Registry (CCR) database and other cases through referrals from the community where the study was conducted.…”
Section: Methodsmentioning
confidence: 99%
“…We included 30 participants, 15 CRC cases and 15 matched family/friend controls by accessing the California Cancer Registry (CCR) database and other cases through referrals from the community where the study was conducted. The designated Human Subjects Institutional Review Boards (IRB) from the local educational institutions and the California State Committee for the Protection of Human Subjects (CPHS 12-12-1007) approved the project [ 43 , 52 ]. With the approved study procedures, the qualified participants were recruited.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These indices consider the whole diet rather than its individual components. DDS along with AHEI have been shown as a measure of healthy diet rich in fruits, vegetables and photochemicals (13)(14)(15) . Although different measures of diet have been linked with cancers, no study examined these indicators in relation to glioma.…”
mentioning
confidence: 99%